"A brief discourse of rebellion and rebels" by George North a newly uncovered manuscript source for Shakespeare's plays - McCarthy, Dennis 1964-; Schlueter, June 1942-; North, George (D.S. Brewer in association with the British Library, 2018)
A new source for Shakespeare's plays, only recently uncovered, is investigated here with a full edition and facsimile of the text
Title from publisher's bibliographic system (viewed on 11 Oct 2019)
Keywords: North, George / gentleman / Brief discourse of rebellion and rebels; Shakespeare, William / 1564-1616 / Sources; Shakespeare, William -- 1564-1616; North, George; Rezeption; Quelle